2015
DOI: 10.4049/jimmunol.1500124
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neutrophilic Inflammation by Proteinase-Activated Receptor 1 during Bacterial Pulmonary Infection

Abstract: Neutrophils are key effector cells of the innate immune response to pathogenic bacteria, but excessive neutrophilic inflammation can be associated with bystander tissue damage. The mechanisms responsible for neutrophil recruitment to the lungs during bacterial pneumonia are poorly defined. In this study, we focus on the potential role of the major high-affinity thrombin receptor, proteinase-activated receptor 1 (PAR-1), during the development of pneumonia to the common lung pathogen Streptococcus pneumoniae. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 58 publications
2
58
1
Order By: Relevance
“…These negative trial data may temper enthusiasm for ongoing research in this area. Nonetheless, PAR-1 antagonism has recently shown beneficial effects on neutrophil migration, cytokine release and barrier disruption in a murine pneumonia model160 suggesting that alternative targets in the pathway may hold therapeutic promise.…”
Section: Modulation Of the Coagulation Cascadementioning
confidence: 99%
“…These negative trial data may temper enthusiasm for ongoing research in this area. Nonetheless, PAR-1 antagonism has recently shown beneficial effects on neutrophil migration, cytokine release and barrier disruption in a murine pneumonia model160 suggesting that alternative targets in the pathway may hold therapeutic promise.…”
Section: Modulation Of the Coagulation Cascadementioning
confidence: 99%
“…After challenge with lipopolysaccharide (LPS) or live bacteria, CCL2 and CCL7 were rapidly upregulated in the lungs, the CC chemokine receptors CCR1 and CCR2 were expressed on neutrophils, and blockade of CCL2 and/or CCL7 attenuated neutrophil recruitment 17 18…”
mentioning
confidence: 99%
“…In addition, the cellular sources of CCL2 and CCL7 and the mechanisms that induce their synthesis are not completely understood. Reports suggest the alveolar and bronchial epithelium as likely sources,17 23 25 and expression appears to be regulated by proteinase-activated receptors 17 18. In addition, while the authors have demonstrated that CCL2/7 are directly chemotactic for neutrophils, there may be additional mechanisms through which CCL2/7 induce neutrophil recruitment, such as via activation of resident alveolar macrophages or epithelial cells to secrete CXC chemokines or by inducing monocyte recruitment, which in turn may facilitate neutrophil recruitment 26.…”
mentioning
confidence: 99%
“…In a model of glomerulonephritis, thrombin induced PAR-1-dependent inflammation [12]. In an infectious model with Streptococcus pneumoniae , antagonizing PAR-1 reduced neutrophil recruitment [13]. During lethal sepsis, dendritic cells (DCs) expressing PAR-1 amplified both inflammatory and thrombotic responses through the sphingosine-1-phosphate 3 (S1P3) signaling pathway [14].…”
Section: Vertebrate Clotting Cascade Can Directly Coordinate Inflammamentioning
confidence: 99%